Radiation refrigeration coating with recyclable function and preparation method thereof

By introducing GLM crosslinking agent and SiO2@APTES, a recyclable radiation cooling coating was developed, which solves the environmental pollution problem of traditional coatings being difficult to recycle. It achieves the unity of high-efficiency cooling and recyclability, and is suitable for industrial plants and large warehouse substrate surfaces.

CN121271428BActive Publication Date: 2026-03-17SOUTHWEST PETROLEUM UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511843841.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-09
Publication Date
2026-03-17
Estimated Expiration
2045-12-09

AI Technical Summary

Technical Problem

Traditional radiation cooling coatings are difficult to recycle at the end of their lifespan, leading to environmental pollution problems.

Method used

By introducing GLM crosslinking agent and modified hollow silica microspheres (SiO2@APTES), a reversible phase transition is achieved under thermal stimulation, which endows the coating with recyclable properties and improves its radiative cooling capacity.

Benefits of technology

It achieves a balance between the recyclability of the coating and its high-efficiency refrigeration performance, solving the environmental pollution problem while maintaining the durability and refrigeration effect of traditional coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121271428B_ABST
    Figure CN121271428B_ABST
Patent Text Reader

Abstract

The application discloses a radiation refrigeration coating with a recyclable function and a preparation method thereof, and belongs to the technical field of refrigeration coatings.The coating is composed of base oil 500SN, hollow silica microspheres (SiO2@APTES) modified by a silane coupling agent, a liquid metal-based crosslinking agent (GLM) composed of a self-prepared urea-based monomer (UM), cetyl methacrylate (CMA) modified liquid gallium (Ga), talcum powder, calcium carbonate, ethylene glycol butyl ether, polyacrylate, methyl ethyl ketone oxime and methyl methacrylate.The GLM crosslinking agent in the coating has a reversible thermal stimulation response, can reversibly perform phase conversion under thermal stimulation, and simultaneously endows the coating with recyclable performance.Meanwhile, the introduction of the SiO2@APTES realizes high reflection of sunlight and high emission of a medium and far infrared band, and guarantees excellent radiation refrigeration performance of the coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of materials preparation technology, and in particular to a recyclable radiation-cooling coating and its preparation method. Background Technology

[0002] Radiation cooling technology, as a passive cooling method with zero energy consumption and zero emissions, has received widespread attention from the global scientific research and industry communities in recent years. Its basic principle is to enhance thermal radiation in a specific wavelength band, directly releasing heat into the cold outer space, while efficiently reflecting sunlight, thereby achieving a cooling effect below the ambient temperature.

[0003] Traditional oil-based radiation cooling coatings offer significant energy savings during their service life, but their non-recyclability presents environmental challenges throughout their entire lifecycle. Industrial-grade radiation cooling coatings typically employ a multi-layer design, consisting of an anti-corrosion underlayer, a reflective intermediate layer, and a radiation cooling surface layer. For example, composite systems based on acrylic-modified polyurethane form a stable three-dimensional network structure through chemical cross-linking. While this structure provides excellent performance, it also results in tightly bonded layers, making effective separation and recycling difficult at the end of their lifespan. After the coating's lifespan, polymers containing perfluoroalkyl substances are difficult to degrade in the environment. Most of these non-recyclable waste coatings end up in landfills, not only consuming land resources but also potentially causing long-term pollution of soil and water sources due to the leakage of hazardous substances. Summary of the Invention

[0004] This invention aims to provide a recyclable radiation-cooling coating and its preparation method. A recyclable oil-based radiation-cooling coating has been developed. The GLM crosslinking agent introduced into the coating undergoes a reversible phase transition under thermal stimulation, endowing it with recyclability. Furthermore, the introduction of silane coupling agent-modified hollow silica microspheres (SiO2@APTES) further enhances the material's radiation-cooling capacity, making it suitable for applications on industrial plant and large warehouse substrates. This coating maintains the high-efficiency cooling performance and durability of traditional oil-based coatings while solving the recycling and reuse problem at the end of its life cycle, achieving a balance between technical performance and environmental benefits.

[0005] The present invention discloses a recyclable radiation-cooling coating and its preparation method, which specifically includes the following steps:

[0006] S1. Mix dichloromethane solution (DCM) and octadecylamine (ODA) thoroughly and add isocyanate methacrylate (MOI). After the reaction is complete, wash the mixture with DCM and dry to obtain urea monomer (UM).

[0007] S2. The mixture of liquid metal (Ga), anhydrous ethanol and deionized water is ultrasonically mixed to obtain a suspension;

[0008] S3. Mix UM, cetyl methacrylate (CMA), 1-ethyl-2,3-dimethylimidazolium p-toluenesulfonate (ILS), ammonium persulfate (APS), sodium bisulfite (SBS), dimethyl sulfoxide (DMSO), and the suspension obtained in S2 and react at high temperature. After the reaction is complete, wash with DMSO and anhydrous ethanol, dry and grind to obtain GLM crosslinking agent.

[0009] S4. Hollow silica microspheres (SiO2) and 3-aminopropyltriethoxysilane (APTES) were added to a mixed solution of anhydrous ethanol and deionized water. The pH was then adjusted to 5-6 with acetic acid. After stirring evenly, an amino-functionalized hollow silica (SiO2@APTES) solution was obtained. Finally, after centrifugation, washing and drying, SiO2@APTES powder was obtained.

[0010] S5. Mix SiO2@APTES, GLM crosslinking agent, methyl methacrylate, talc, calcium carbonate, methyl ethyl ketone oxime, ethylene glycol butyl ether and base oil 500SN evenly to prepare a radiation cooling coating.

[0011] As a further improvement of the present invention, the molar ratio of MOI and ODA in step S1 is 1:1, and when both are taken at 0.05 mol, the DCM is 250 ml; the specific conditions for stirring and mixing in step S1 are magnetic stirring at 400~800 rpm for 2~4 h at room temperature; the specific conditions for drying in step S1 are drying in a vacuum environment at 60 ℃ for 24 h.

[0012] As a further improvement of the present invention, in step S2, the volume ratio of anhydrous ethanol to deionized water is 1:1, and the proportion of liquid metal Ga in the mixed solution is 3.0~5.0wt%; the ultrasound in step S2 is specifically performed in an ice-water bath, with an ultrasound interval of 0.2~0.4s, an ultrasound power of 70~90% of 1200 W, and an ultrasound time of 20-30min.

[0013] As a further improvement of the present invention, in step S3, the molar ratio of UM, CMA, ILS, APS, SBS and liquid Ga in the suspension is 10:10:(6~8):1:1:(20~30); the high-temperature reaction in step S3 is specifically carried out under nitrogen at 85°C for 24 hours with a stirring speed of 300~500 rpm; the washing in step S3 is specifically carried out by washing once with DMSO and then twice with anhydrous ethanol; the drying in step S3 is specifically carried out by drying in a vacuum environment at 30°C for 24 hours; the grinding in step S3 is specifically carried out by grinding at room temperature for 3~5 hours.

[0014] As a further improvement of the present invention, the mass ratio of SiO2 to APTES in step S4 is 1:0~1.5; the volume ratio of anhydrous ethanol to deionized water in the mixed solution in step S4 is 9:1; the stirring in step S4 is carried out under the following conditions: at room temperature, magnetic stirring at 300~500 rpm for 20~60 min; centrifugation in step S4 is carried out under the following conditions: centrifugation at 10000 rpm for 10~20 min; washing in step S4 is carried out under the following conditions: washing 3~5 times in anhydrous ethanol; drying in step S4 is carried out under the following conditions: drying at a temperature of 50~70 ℃ and a pressure of -0.08 Pa for 12~24 h.

[0015] As a further improvement of the present invention, in step S5, the radiation cooling coating contains SiO2@APTES at a ratio of 15.0~25.0 wt%, GLM crosslinking agent at a ratio of 3.0~5.0 wt%, methyl methacrylate at a ratio of 0.2~1.0 wt%, talc and calcium carbonate at a ratio of 10~25 wt%, base oil 500SN at a ratio of 30~45 wt%, ethylene glycol butyl ether at a ratio of 2.0~5.0 wt%, and methyl ethyl ketone oxime at a ratio of 0.1~0.5 wt%. In step S5, the mixture is stirred evenly under the following conditions: at room temperature, mechanically stirred at a speed of 300~700 rpm for 10~20 min.

[0016] As a further improvement of the present invention, the GLM crosslinking agent has a particle size of 2-5 μm, and the coating is used to form a radiation cooling coating on the surface of the substrate, wherein the radiation cooling capacity of the material is further improved due to the introduction of SiO2@APTES.

[0017] As a further improvement of the present invention, the radiation cooling coating is characterized by having reversible temperature responsiveness, being able to achieve reversible melt-solidification conversion at 60°C, thus giving it special recyclability.

[0018] As a further improvement of the present invention, the radiation cooling coating is characterized in that it is used on the substrate surface of industrial plants and large warehouses.

[0019] Compared with the prior art, the advantages of the present invention are as follows:

[0020] (1) The GLM crosslinking agent prepared by the present invention has a reversible melt-solidification transition. The GLM crosslinking agent has extremely strong fluidity when heated to 60°C and no fluidity when cooled to 20°C. In addition, the GLM crosslinking agent has good dispersibility in radiation cooling coatings. Therefore, due to its special properties, the problem of recycling and reuse after the end of the life cycle is solved, and the unity of technical performance and environmental benefits is achieved.

[0021] (2) The coating prepared by this invention has excellent cooling performance. In a model without coating, under a light intensity of 200 mW / cm², 2 After 3 hours of irradiation, its internal temperature was 42.4℃, while the temperature of the coated model part was 33℃, which enhanced its application performance. Attached Figure Description

[0022] Figure 1 This is a flowchart illustrating the preparation process of a recyclable radiation-cooling coating and its preparation method according to the present invention.

[0023] Figure 2 The images show the radiation-cooling coating before and after heating. (a) is a picture of the coating at room temperature, and (b) is a picture of the coating after heating to 60°C.

[0024] Figure 3 (a) and (b) are at 200 mW / cm 2 The temperature changes inside the model without coating and the model with coating were measured after 3 hours of irradiation under light intensity. (c) and (d) are a panoramic view and a magnified view of the test equipment, respectively.

[0025] Figure 4 The images show the SEM and EDS test results of the GLM crosslinking agent prepared in Example 1.

[0026] Figure 5 The image shows the SEM test results of the SiO2@APTES-0.75 powder prepared in Example 2.

[0027] Figure 6 (a) and (b) are X-ray diffraction (XRD) images of Ga, GLM crosslinking agent and SiO2, SiO2@APTES powder prepared in Examples 1 and 2, respectively.

[0028] Figure 7 The total spectrum test results of X-ray photoelectron spectroscopy (XPS) of the GLM crosslinking agent and SiO2@APTES-0.75 prepared in Examples 1 and 2.

[0029] Figure 8 The infrared spectra of SiO2@APTES and radiation-cooled coating prepared in Example 1 are shown. Detailed Implementation

[0030] This invention provides a recyclable coating for radiative cooling and a method for preparing the same. To make the objectives, technical solutions, and advantages of this invention clearer and more explicit, the invention will be further described in conjunction with specific embodiments and accompanying drawings.

[0031] Example 1

[0032] like Figure 1 As shown, the present invention discloses a recyclable radiation cooling coating and its preparation method, which are prepared through the following steps:

[0033] Step 1: Add 13.48 g of ODA to a container containing 250 mL of DCM. Stir continuously at 400 rpm for 30 min at room temperature. Then, add 7.76 g of MOI dropwise to the above solution and stir for 2 h. After the reaction is complete, wash the white solid with DCM. Finally, dry the washed white solid in a vacuum environment at 35°C for 12 h to successfully obtain the UM monomer.

[0034] Step 2: Add 200 mg of liquid gallium (Ga) to a mixed solution of 2.5 mL of anhydrous ethanol and 2.5 mL of deionized water, and sonicate at 300 W for 1 h under ice-water bath conditions to obtain gallium-based liquid metal nanosuspension (GLM nanosuspension).

[0035] Step 3: 764.4 mg UM monomer, 609.4 mg CMA, 151.3 mg ILS, 28.0 mg APS, 11.0 mg SBS, and the GLM nano-suspension prepared above were added to 25 mL DMSO. The mixture was subjected to free radical polymerization at 85 °C for 24 h. After the reaction, the product was dried in a vacuum environment at 30 °C for 24 h to obtain a dark gray solid GLM crosslinking agent.

[0036] Step 4: Disperse 1 g of hollow silica microspheres in 50 mL of anhydrous ethanol and sonicate for 30 minutes. Add 1.5 mL of APTES to 50 mL of ethanol / water mixed solvent (volume ratio 9:1), and adjust the pH to 5-6 by adding acetic acid dropwise. React in a constant temperature water bath at 70℃ for 4 hours. After the reaction is complete, vacuum dry the product at 60℃ for 12 hours to obtain amino-functionalized hollow silica microspheres (SiO2@APTES).

[0037] Step 5: Add 45 parts of base oil 500SN to the mixing tank, then add 25 parts of SiO2@APTES, 5 parts of GLM crosslinking agent, 1 part of methyl methacrylate, 10 parts of talc and calcium carbonate, and 5 parts of ethylene glycol butyl ether in sequence. Stir at 600 rpm for 5 minutes under stirring conditions to obtain the radiation cooling coating.

[0038] Example 2

[0039] Example 2 provides a recyclable radiation cooling coating and its preparation method. Compared with Example 1, the difference is that in step 4, the volumes of APTES are 0.25 ml, 0.5 ml and 0.75 ml, respectively. The rest is the same as in Example 1 and will not be repeated here. SiO2@APTES-0.25, SiO2@APTES-0.5 and SiO2@APTES-0.75 powders are obtained.

[0040] Figure 2 The introduction of GLM crosslinking agent reveals that the coating exhibits temperature responsiveness, enabling a reversible melt-solidification transition at 60°C. The coating also demonstrates strong fluidity at 60°C, thus achieving recyclability.

[0041] Figure 3 The introduction of SiO2@APTES revealed that it enhanced the radiative cooling capacity of the coating, as demonstrated in the uncoated model under illumination of 200 mW / cm². 2 After 3 hours of irradiation, its internal temperature was 42.4℃, while the temperature of the coated model part was only 33℃.

[0042] The prepared GLM crosslinking agent was subjected to SEM testing and corresponding energy dispersive spectroscopy (EDS). The prepared SiO2@APTES powder was also subjected to SEM testing, and the results are as follows: Figure 4 and Figure 5 As shown in the figure, the GLM crosslinking agent is at the micron level with a particle size of 2-5 μm and contains a large amount of gallium, which is beneficial for phase transformation. The SiO2@APTES powder is at the micron level with a particle size of 3-6 μm.

[0043] X-ray diffraction (XRD) analysis was performed on the prepared Ga, GLM crosslinking agent, SiO2, and SiO2@APTES samples, and the results are as follows: Figure 6 As shown in (a) and (b); X-ray photoelectron spectroscopy (XPS) was also performed on the GLM crosslinking agent and SiO2@APTES, as shown in... Figure 7 As shown. Comparison of the XRD patterns of Ga and GLM crosslinking agent reveals that the characteristic peaks of GLM crosslinking agent match those of Ga within a certain diffraction angle range, indicating that CMA has successfully modified and coated Ga, and no significant diffraction signal appears after 30°. Further comparison of the XRD patterns of SiO2 and SiO2@APTES reveals that the 15–30° range contains typical broad scattering peaks of amorphous SiO2, while the diffraction peaks of SiO2@APTES are significantly broader than those of SiO2, indicating that the introduction of APTES leads to a reduction in grain size and a refinement of the structure. In addition, XPS analysis results ( Figure 7 This further confirms that APTES has been successfully grafted onto the SiO2 surface, thus verifying the effective modification of the GLM crosslinking agent.

[0044] Figure 8 Comparative analysis of the infrared spectra of SiO2@APTES and radiation-cooled coatings revealed that SiO2@APTES exhibits higher infrared spectral density at 1110 cm⁻¹. -1 The strong absorption peak at 803 cm⁻¹ is attributed to the C–O stretching vibration, while the peak at 803 cm⁻¹ is attributed to the C–O stretching vibration. -1 The absorption peak at 1110 cm⁻¹ corresponds to the benzene ring structure. In radiation-cooled coatings, the absorption peak at 1110 cm⁻¹ corresponds to the benzene ring structure. -1 The characteristic absorption peak at 2921 cm⁻¹ disappeared significantly, a phenomenon that may be related to the amount of SiO₂@APTES added. Furthermore, the GLM coating showed a significant reduction in peak density at 2921 cm⁻¹. -1 2851 cm -1 1458 cm -1 and 1374 cm -1 Several absorption peaks also appeared in the coating, which can be attributed to the introduction of GLM crosslinking agent and 500SN base oil in the coating.

[0045] The above embodiments are only used to illustrate preferred embodiments of the present invention and do not constitute a limitation on the scope of protection of the present invention. Any modifications, equivalent substitutions, or optimizations made within the technical concept and principle framework of the present invention should be considered to fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a radiation refrigeration coating with recyclable function, specifically comprising the following steps: S1, stirring and mixing dichloromethane solution (DCM) and octadecylamine (ODA) uniformly and adding isocyanomethyl methacrylate (MOI), after complete reaction, washing the mixed solution with DCM and drying to obtain urea-based monomer (UM); S2, ultrasonic mixing the mixed solution of liquid metal (Ga), anhydrous ethanol and deionized water to obtain a suspension; S3, mixing UM, cetyl methacrylate (CMA), 1-ethyl-2,3-dimethyl imidazole p-toluenesulfonate (ILS), ammonium persulfate (APS) and sodium bisulfite (SBS), dimethyl sulfoxide (DMSO) and the suspension obtained in S2 to react at high temperature, after the reaction is completed, washing with DMSO and anhydrous ethanol, drying and grinding to obtain GLM crosslinking agent; S4, adding hollow silica microspheres (SiO2) and 3-aminopropyl triethoxysilane (APTES) to the mixed solution of anhydrous ethanol and deionized water, then adjusting the pH to 5-6 with acetic acid, stirring uniformly to obtain an amino-functionalized hollow silica (SiO2@APTES) solution, and finally obtaining SiO2@APTES powder after centrifugation, washing and drying; S5, mixing SiO2@APTES, GLM crosslinking agent, methyl methacrylate, talc, calcium carbonate, methylethyl ketone oxime, ethylene glycol butyl ether and base oil 500SN uniformly to prepare a radiation refrigeration coating.

2. The preparation method of the radiation refrigeration coating with recyclable function according to claim 1, characterized in that, The molar ratio of MOI and ODA in step S1 is 1:1, and when both are 0.05 mol, DCM is 250 ml; the stirring and mixing in step S1 is specifically 2-4 h of magnetic stirring at room temperature at a speed of 400-800 rpm; the drying in step S1 is specifically 24 h of drying in a vacuum environment at a temperature of 60℃.

3. The preparation method of the radiation refrigeration coating with recyclable function according to claim 1, characterized in that, The volume ratio of anhydrous ethanol and deionized water in step S2 is 1:1, and the proportion of liquid metal Ga in the mixed solution is 3.0-5.0wt%; the ultrasonic in step S2 is specifically 20-30 min of ultrasonic at an interval of 0.2-0.4 s, a power of 70-90% of 1200 W and in an ice water bath.

4. The preparation method of the radiation refrigeration coating with recyclable function according to claim 1, characterized in that, The molar ratio of UM, CMA, ILS, APS, SBS and the liquid Ga in the suspension in step S3 is 10:10:(6-8):1:1:(20-30); the high temperature reaction in step S3 is specifically 24 h of stirring at a speed of 300-500 rpm at 85℃ under nitrogen; the washing in step S3 is specifically 1 time of DMSO washing and 2 times of anhydrous ethanol washing; the drying in step S3 is specifically 24 h of drying in a 30℃ vacuum environment; the grinding in step S3 is specifically 3-5 h of grinding at room temperature.

5. The preparation method of the radiation refrigeration coating with recyclable function according to claim 1, characterized in that, The mass ratio between SiO2 and APTES in the step S4 is 1:0-1.5; the volume ratio of anhydrous ethanol and deionized water in the mixed solution in the step S4 is 9:1; the stirring in the step S4 is uniform, and the specific conditions are magnetic stirring at room temperature at a speed of 300-500 rpm for 20-60 min; the centrifugation in the step S4 is 10-20 min at 10000 rpm; the washing in the step S4 is 3-5 times in anhydrous ethanol; and the drying in the step S4 is at a temperature of 50-70 ℃ and a pressure of-0.08 Pa for 12-24 h.

6. The preparation method of the radiation refrigeration coating with recyclable function according to claim 1, characterized in that, The SiO2@APTES in the radiation cooling coating in the step S5 is 15.0-25.0 wt%, the GLM crosslinking agent is 3.0-5.0 wt%, the methyl methacrylate is 0.2-1.0 wt%, the talc and calcium carbonate are 10-25 wt%, the base oil 500SN is 30-45 wt%, the ethylene glycol butyl ether is 2.0-5.0 wt%, the methyl ethyl ketone oxime is 0.1-0.5 wt%, and the mixing in the step S5 is uniform, and the specific conditions are mechanical stirring at room temperature at a speed of 300-700 rpm for 10-20 min.

7. A radiative cooling paint having a recyclable function, characterized by, Prepared by the preparation method of any one of claims 1-6.

8. The radiative cooling coating with recyclable function according to claim 7, characterized in that, The GLM crosslinking agent has a particle size of 2-5 μm, and the coating is used to form a radiation cooling coating on the surface of a substrate, wherein the introduction of SiO2@APTES further improves the radiation cooling capacity of the material.

9. The radiative cooling coating with recyclable function according to claim 7, characterized in that The radiation cooling coating has reversible temperature responsiveness and can realize reversible melting-solidification conversion at 60 ℃, thereby giving it special recyclability.

10. The radiative cooling coating with recyclable function according to claim 7, characterized in that The radiation cooling coating is used on the surface of a substrate of an industrial plant and a large warehouse.

Citation Information

Patent Citations

  • Porous titanium carbide MXene / reduced graphene oxide based wallboard

    CN112443051A

  • Liquid metal-based ionic oil gel lubricant as well as preparation method and application thereof

    CN118834717A